Genotypic Variation in Cultivated and Wild Sorghum Genotypes in Response to Striga hermonthica Infestation - Muchira, Nicoleta; Ngugi, Kahiu; Wamalwa, Lydia N.; Avosa, Millicent; Chepkorir, Wiliter; Manyasa, Eric; Nyamongo, Desterio; Odeny, Damaris A. (Frontiers in Plant Science, 2021)
Striga hermonthica is the most important parasitic weed in sub-Saharan Africa and remains one of the most devastating biotic factors affecting sorghum production in the western regions of Kenya. Farmers have traditionally managed Striga using cultural methods but the most effective and practical solution to poor smallholder farmers is to develop Striga resistant varieties. This study was undertaken with the objective of identifying new sources of resistance to Striga in comparison with the conventional sources as standard checks. We evaluated 64 sorghum genotypes consisting of wild relatives, landraces, improved varieties and F4 progenies in a field trial and in a pot trial. Data were taken for days to 50% flowering (DTF), dry panicle weight (DPWT; g), plant height (PH; cm), yield (YLD; t ha-1) and 100-grain weight (HGW; g), overall disease score (ODS), overall pest scores (OPS), area under Striga number progress curve (ASNPC), maximum above ground Striga (NSmax) and number of Striga forming capsules (NSFC) at relevant stages. Genetic diversity and hybridity confirmation was determined using Diversity Arrays Technology (DArT) sequencing. Residual heterosis for HGW and NSmax were calculated as the percent increase or decrease in performance of F4 cross over mid-parent. The top ten best yielding genotypes were predominantly F4 crosses in both experiments, all of which yielded better than resistant checks, except FRAMIDA in the field trial and HAKIKA in the pot trial. Five F4 progenies (ICSVIII IN x E36-1, LANDIWHITE x B35, B35 x E36-1, F6YQ212 x B35 and ICSVIII IN x LODOKA) recorded some of the highest HGW in both trials revealing their stability in good performance. Three genotypes (F6YQ212, GBK045827 and F6YQ212xB35) and one check (SRN39) were among the most resistant to Striga in both trials. SNPs generated from DArT-sequencing grouped the genotypes into three clusters, with resistant checks grouping in the same cluster except N13. We identified more resistant and high yielding genotypes than the conventional checks, especially among the F4 crosses. Future studies will need to look for more diverse sources of Striga resistance and pyramid different mechanisms of resistance into farmer-preferred varieties to enhance the durability of Striga resistance.